Produção e caracterização de anticorpos monoclonais anti épsilon toxina de Clostridiun perfrigens tipo D - Theonys Diogenes Freitas (2006)
Monoclonal antibodies reactive against épsilon toxin from Clostridium perfringens type D were produced. Myeloma cell lines Sp2/0. Ag14 and P3-X63-Ag8.653 were fused with spleen cells from mice BALB/c immunized with epsilon toxoid. After fusion 59 wells were positive for the Sp2/0. Ag14 cell line and 19 for the P3-X63-Ag8.653, representing 6.68 and 6.59% respectively. Six hybrids were established secreting MoAb of the IgM (k) class and IgG3 (k) subclass. An average of 21.52 g/ml of IgM and 15 g/ml of IgG3 anti-epsilon toxin MoAb were obtained from the hybrids culture supernatant